Bladder Lymphangioma Treated by Holmium Laser: Extremely Rare Case Report - Moradi, Asad; Kazemzadeh Azad, Babak; Fasihi, Mahyar; Aliakbari, Fereshteh (Journal of Lasers in Medical Sciences, 2020)
Introduction: Lymphangioma is a sporadic benign tumor of the bladder. It is a congenital disorder and based on the size of lymphatic spaces, it is divided into 3 types of capillary, cavernous, and cystic. Case Report: In this paper, we presented a 40-year-old woman with microscopic hematuria and a normal urinary ultrasound. Urethrocystoscopy showed a flat 4 mm highlighted strawberry-like lesion on the right lateral wall of the bladder. After a cold cup biopsy, the lesion was coagulated by the holmium: YAG (Ho: YAG) laser. Conclusion: In Bladder Lymphangioma Based on the size of the lesion, partial cystectomy or minimally invasive surgeries such as laser modality would be the principal treatment.